The BpMYB4 Transcription Factor From Betula platyphylla Contributes Toward Abiotic Stress Resistance and Secondary Cell Wall Biosynthesis - Yu, Ying; Liu, Huizi; Zhang, Nan; Gao, Caiqiu; Qi, Liwang; Wang, Chao (Frontiers in Plant Science, 2021)
The MYB (v-myb avian myeloblastosis viral oncogene homolog) family is one of the largest transcription factor families in plants, and is widely involved in the regulation of plant metabolism. In this study, we show that a MYB4 transcription factor, BpMYB4, identified from birch (Betula platyphylla Suk.) and homologous to EgMYB1 from Eucalyptus robusta Smith and ZmMYB31 from Zea mays L. is involved in secondary cell wall synthesis. The expression level of BpMYB4 was higher in flowers relative to other tissues, and was induced by artificial bending and gravitational stimuli in developing xylem tissues. The expression of this gene was not enriched in the developing xylem during the active season, and showed higher transcript levels in xylem tissues around sprouting and near the dormant period. Functional analysis indicated that expression of BpMYB4 in transgenic Arabidopsis (Arabidopsis thaliana) plants could promote the growth of stems, and result in increased number of inflorescence stems and shoots. Anatomical observation of stem sections showed lower lignin deposition, and a chemical contents test also demonstrated increased cellulose and decreased lignin content in the transgenic plants. In addition, treatment with 100 mM NaCl and 200 mM mannitol resulted in the germination rate of the over-expressed lines being higher than that of the wild-type seeds. Further investigation in birch using transient transformation techniques indicated that overexpression of BpMYB4 could scavenge hydrogen peroxide and O2.- and reduce cell damage, compared with the wild-type plants. Therefore, we believe that BpMYB4 promotes stem development and cellulose biosynthesis as an inhibitor of lignin biosynthesis, and has a function in abiotic stress resistance.